EXPERIENCE WITH ENDOSCOPY AT BIN JALAWI HOSPITAL K.S.A. - Rabbani, Aftab (Journal of Ayub Medical College Abbottabad, 2005)
Background: Presentation of gastrointestinal disorders may vary in different communities. This study was carried out in town of Hafoof in Eastern zone of Saudi Arabia. Purpose of the study was to observe pattern of presentation, age, sex, smoking status, haemoglobin levels, serological markers for hepatitis, endoscopic findings, histopathology, presence of H. Pylori or otherwise in biopsy materials taken during the endoscopic procedures in patients undergoing endosopic examinations. Findings of 230 endoscopies are presented. Methods: All patients who underwent endoscopy in Bin Jalawi Hospital KSA, between December 1999 and September 2001 were included in the study. Data regarding above mentioned features was collected. Patients under went gastroscopy, colonoscopy and injection sclerotherapy. Biopsies were taken and histopathological studies were carried out. Results: Data of 187 gastroscopies, 12 sclerotherapy sessions and 31 sigmoidoclonoscopies is presented. Antral Gastritis was most commonly seen pathology. Gastric and esophageal varices, erosive gastritis, carcinoma oesophagus, duodenitis and oesophagitis were among the other common pathologies. Age of the subjects ranged between 15 and 80 years. Hepatitis B surface antigen was detected in 13 Patients and Hepatitis C antibodies were reported positive in 21 samples. Conclusions: This data reflects pattern of findings encountered on endoscopies in Hafoof area of KSA, this may assist in comparing the pattern of presentation in this centre with other centers within and outside Saudia. Key Words: Endoscopy, Gastrointestinal disorders, Gastritis, Oesophagitis,